High-precision time-domain stereoscopic imaging with a femtosecond electro-optic comb - Zijian Wang; Hui Ma; Jingwei Luo; Ming Yan; Kun Huang; Jianan Fang; Jinman Ge; Heping Zeng (Nature Communications)
Abstract Stereoscopy harnesses two spatially offset cameras to mimic human vision for depth perception, enabling 3D optical imaging for various remote sensing applications. However, its depth precision and accuracy are limited by insufficient spatial resolving power. Achieving high precision alongside extensive measurable ranges and high-speed measuring capabilities has long been a challenge in 3D imaging. To address this, we introduce time-domain stereoscopy, a concept inspired by space-time duality in optics. Specifically, it employs two temporally offset optical gating cameras to capture time-domain parallax signals, enabling rapid and precise time-of-flight measurements for depth retrieval. Leveraging two advanced technologies—femtosecond electro-optical comb synthesis and nonlinear optical sampling—this method achieves sub-100-nanometer depth precision across multimeter-scale imaging ranges and supports millisecond-scale displacement and velocity measurements for 47 million spatial points simultaneously. As such, it provides a versatile tool for applications in surface metrology, mechanical dynamics, and precision manufacturing.